The extent of the independence of the statutory auditors according to law 10-01 - KADRI, Abdelmadjid (Journal of Human Sciences, 2020)
The auditor certifies the accounts published by the enterprise, that is to say that the latter correspond to the financial reality of the enterprise. This certification is very important for financial markets and the economy in general.The independence of the auditor is seen as an essential tool for restoring public confidence in the reliability and credibility of financial information. It must enjoy absolute independence from the shareholders as well as from the managers and managers of the audited information.The introduction of the principle of the independence of the auditor may be justified, on the one hand, by the very extensive powers held by the directors of the undertaking, and on the other, in order to defend the interests of employees, which can only be carried out with the intervention of a neutral opinion